1996
DOI: 10.1002/j.1552-4604.1996.tb05040.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Inhibition of Inducible Cyclooxygenase by Chiral Nonsteroidal Antiinflammatory Drugs

Abstract: The stereoselective inhibition of inducible cyclooxygenase (COX-2) by chiral nonsteroidal antiinflammatory drugs (NSAIDs)--ketoprofen, flurbiprofen, and ketorolac--has been investigated. The activity and inhibition of COX-2 was assessed in three different in vitro systems: guinea pig whole blood, lipopolysaccharide (LPS)-stimulated human monocytes, and purified preparations of COX-2 from sheep placenta. The results were compared with the inhibition of constitutive cyclooxygenase (COX-1) in three parallel in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 39 publications
3
75
1
2
Order By: Relevance
“…1995 . Our data also indicate that, although breaking the integrity of the cell plasma membrane should facilitate the access of metamizol to the endoplasmic reticulum and nuclear envelope, where cyclooxygenase-2 is located Ž . Morita et al, 1995 , cell purified enzymes have also been described for other Ž NSAIDs Barnett et al, 1994;Mitchell et al, 1994;. Carabaza et al, 1996 .…”
Section: Discussionmentioning
confidence: 99%
“…1995 . Our data also indicate that, although breaking the integrity of the cell plasma membrane should facilitate the access of metamizol to the endoplasmic reticulum and nuclear envelope, where cyclooxygenase-2 is located Ž . Morita et al, 1995 , cell purified enzymes have also been described for other Ž NSAIDs Barnett et al, 1994;Mitchell et al, 1994;. Carabaza et al, 1996 .…”
Section: Discussionmentioning
confidence: 99%
“…And, the reduction of C cr was observed for (S)-flurbiprofen but not for the (R)-enantiomer. Carabaza et al [6] examined the inhibitory effects of the flurbiprofen enantiomers on cyclooxygenase (COX)-1 and COX-2 and reported that the IC 50 values for the (R)-enantiomer were 100-fold greater than those for (S)-flurbiprofen. These are suggested to be the molecular mechanisms for the findings obtained in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that first of all, SFP potently inhibited PGE 2 production from peritoneal leukocytes stimulated with a bacterial suspension; its inhibitory activity against PGE 2 production in a rat intact cell model was a 1000-fold more potent than that of RFP and also exhibited stereoselectivity. In human polymorphonuclear cell models, SFP was shown to potently inhibit PG production (IC 50 = 2.7 nM for SFP and 400 nM for SFP, respectively; RFP/SFP inhibitory ratio = 148) [5]. Our results suggested that the inhibitory activity of SFP in human polymorphonuclear cells was nearly as effective as the inhibitory activity of SFP in the rat peritoneal leukocytes.…”
Section: Discussionmentioning
confidence: 59%
“…In the past, the 2-aryl propionic acid NSAIDs were developed in the form of a racemic mixture, even though they occurred in enantiomeric pairs differing in the COX inhibitory activity [4] [5]. Flurbiprofen (FP) is a representative drug of the chiral NSAIDs of the 2-arylpropionic acid class, and S(+)-flurbiprofen (SFP) has been shown to be a more potent COX inhibitor than the R(−)-flurbiprofen (RFP) enantiomer.…”
Section: Introductionmentioning
confidence: 99%